2019
DOI: 10.1109/access.2019.2948064
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Flexible Reservations in a Car Sharing System With an Auction Scheme

Abstract: In the last 20 years car sharing has been a growing trend in personal mobility. Multiple aspects of these systems have been already discussed: different forms of car sharing, user's preferences and behavior, or benefits estimation. Nevertheless, the management of these systems needs to be continuously improved to remain a competitive alternative. In this work, we propose a reservation scheme to manage rental reservations of a two-way station-based car sharing system. It allows the operator to better plan the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The design of the underlying blockchain-based platform depends on the five design principles, namely security and privacy, authenticity, traceability and reliability, scalability, and interoperability. [17] A reservation scheme has been proposed for station-based two-way car-sharing systems that leverages the temporal flexibility of drivers. By combining reservations with flexibility, the scheme can benefit both the car-sharing owner and the drivers by improving the management of reservation information.…”
Section: Literature Surveymentioning
confidence: 99%
“…The design of the underlying blockchain-based platform depends on the five design principles, namely security and privacy, authenticity, traceability and reliability, scalability, and interoperability. [17] A reservation scheme has been proposed for station-based two-way car-sharing systems that leverages the temporal flexibility of drivers. By combining reservations with flexibility, the scheme can benefit both the car-sharing owner and the drivers by improving the management of reservation information.…”
Section: Literature Surveymentioning
confidence: 99%
“…e results showed that the influence of spatial flexibility was greater in the latter case. Roca-Riu and Menendez [27] proposed an auction scheme with flexible vehicle reservation time to reduce the fleet size of a two-way station-based car sharing system. Drivers were given individual utility according to their preferences and could choose different travel time flexibilities.…”
Section: Traditional Vehicle Sharing Reservation Servicesmentioning
confidence: 99%
“…Re-balancing re-adjusts vehicle supply for each station to better fit the demand of the car-sharing service, while minimising the fleet size and the number of staff [1], [83]. In an optimised reservation-based system, users need to book their trips in advance, which can effectively increase the level of service [14], [28], [84]. The feedback dynamic pricing methodology [68], [71], [85] has been well studied in the literature for regulating users demand based on the existing car station capacity.…”
Section: A Shared Services Driven By Human 1) Car-sharingmentioning
confidence: 99%